Seleção de genótipos de eucalipto resistentes à ferrugem (Puccinia psidii) através de parâmetros monocíclicos - Ferreira, Karina Carnielli Zamprogno [UNESP]; Marino, Celso Luis [UNESP]; Furtado, Edson Luiz [UNESP] (FapUNIFESP (SciELO), 2017)
Genetic variability within the genus Eucalyptus for resistance to diseases and abiotic factors is present, especially for eucalyptus rust (Puccinia psidii WINTER), the first control measure of which is to prevent commercial planting of susceptible plants. Search for quantitative resistance traits can lead to superior genotypes with durable resistance. This study aimed to identify monocyclic parameters for evaluating rust in eucalyptus, most closely related to genetic resistance, and to establish a ranking of genotypes with greater resistance to rust in order to prepare a breeding program, besides relating the host response to the plant defense pathways. Therefore, a comparative study was conducted between assessment of rust in the field, based on a qualitative disease severity scale, and quantitative monocyclic parameters of the disease in a controlled environment. Prevalence of susceptible individuals indicated possible segregation distortions, corroborating hypotheses of previous studies. Results showed that the resistance gene present in this population is dependent on the action of other genes that are indirectly related to resistance and that participate in the metabolic defense pathways of Eucalyptus.
Selection of eucalyptus genotypes resistant to rust (Puccinia psidii) using monocyclic parameters
Keywords: Eucalyptus; Heritability; Infective period; Latent period; Phenotipic correlation; Puccinia psidii